Challenges and opportunities for improvement in the management and financing system of Health Promotion Offices in Hungary - Horváth, Krisztián; Túri, Gergo; Kaposvári, Csilla; Cseh, Borbála; Dózsa, Csaba László (Frontiers in Public Health, 2023)
Background: 110 Health Promotion Offices (HPOs) have started operating in Hungary in response to public health challenges. Many of them have been active for almost ten years, but yet their operational experience has not been evaluated. The specific objectives of our study were: (1) to describe the current operational and funding system of HPOs, (2) to identify challenges related to the current management and funding practices, and (3) to formulate recommendations for improvement based on gathered experience and international experience.Design: In order to gain a deeper insight into the operational experience of HPOs, an online survey was conducted with the professional or economic managers of HPOs. A scoping review was carried out to gather international experiences about best practices to formulate recommendations for improvement in developing the operational and financing scheme for HPOs.Results: We found that current HPO network in Hungary faces three main challenges: a deficient management system, inflexible financing scheme, and unequal ability to purchase or provide services for the population.Conclusions: Based on the survey complemented by international experiences, we propose the overhaul of the professional management system and switching to a combination of fixed and performance-based financing scheme for the HPOs in Hungary.